Meningkatkan Motivasi Belajar Siswa Melalui Penggunaan Media Pembelajaran Interaktif Touching Geometry Pada Materi Bangun Ruang Kelas II SDN 4 Ngembal Kulon - Sa’idah, Qoimatul Ulya; Zulfa, Nur Amrina; Fakhru Ahsani, Eva Luthfi (Jurnal Karya Ilmiah Pendidik dan Praktisi SD&MI (JKIPP), 2025)
This study identifies the low motivation of students in Mathematics, particularly in the subject of spatial building in class II SDN 04 Ngembal Kulon. The purpose of the research is to enhance students' motivation through the use of interactive multimedia learning media, Touching Geometry. The method employed is classroom action research conducted in two cycles, with data collection through observation and interviews. The results indicate an increase in students' motivation from 86% in the first cycle to 93.30% in the second cycle. The use of interactive media successfully created an engaging learning environment and actively involved students. The impact of this research is an improvement in students' understanding of spatial building concepts and a positive attitude towards Mathematics. The conclusion of this study asserts that interactive multimedia learning media is effective in increasing student motivation and participation. Keywords: learning motivation; interactive multimedia; spatial building; classroom action research; Mathematics.